PARTISIPASI DAN PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN DAYA TARIK WISATA “RICE TERRACE” CEKING, GIANYAR, BALI - Yulianie, Fatrisia (Jurnal Master Pariwisata (JUMPA); Volume 02, Nomor 01, Juli 2015DO - 10.24843/JUMPA.2015.v02.i01.p11)
This article analyzes about the participation and community empowerment in the management of unique and beautiful tourist attraction of rice terrace in Ceking Village, Gianyar Regency. It also discuses tourists’ opinion to the tourist attraction of Ceking. The theories used in this research are the theory of participation and community management theory. Data were collected through observation, interviews, documentation, and questionnaires. The sampling techniques used were purposive and accidental sampling. Data were analyzed by using descriptive qualitative analysis to give an overview of community empowerment in the management of tourist attraction in the Village of Ceking of Tegallalang, the Gianyar Regency. The finding shows that people around the tourist attraction of Ceking have participated in the development of the tourist attraction. However, the community empowerment of Ceking tourist attraction has not been performed optimally yet, because around the tourist attraction, there are two large communities, namely the villages of Tegallalang and Kedisan. The Kedisan community, as the owner of the rice terrace, has not been optimally empowered and involved in the management and development. Tourists visiting Ceking considered it an interesting tourist attraction to visit, but expressed that the infrastructure and the tourist facilities on the attraction are very poor and need improvement.